WORD FORMATION OF SLANG WORD IN SONG ALBUMS CREATED BY INDONESIAN RAPPER, YOUNG LEX - Astari Putri Raodhatul; Havid Ardi (Universitas Negeri Padang, 2019)
This research is aimed to identify (1) What are the word formation process of the slang word found in the lyrics of “Young Lex” songs (2) What are the common characteristics of slangs found in the lyrics of “Young Lex” songs. The method used in this study is descriptive qualitative method.This research paper usedGeorge Yule (2006) processes of word formation. The researcher found 6 types word formation in slang word in the lyrics of Young Lex among others blending, compounding, clipping, borrowing, coinage and acronym and 1 theory of Elissa Matiello, Variation.The data were collected by listening to 9 songs by Young Lex and reading the lyrics of the songs. There were 27 slang of variation, 6 slang of blending, 11 slang of clipping, 4 slang of compounding, 4 slang coinage, 17 slang borrowing and 6 slang of acronym.